CAMSAP2 is required for bridging fiber assembly to ensure mitotic spindle assembly and chromosome segregation in human epithelial Caco-2 cells. - Naoko Nishizawa; Riku Arai; Koki Hiranuma; Mika Toya; Masamitsu Sato (PLoS ONE)
In mammalian epithelial cells, cytoplasmic microtubules are mainly non-centrosomal, through the functions of the minus-end binding proteins CAMSAP2 and CAMSAP3. When cells enter mitosis, cytoplasmic microtubules are reorganized into the spindle composed of both centrosomal and non-centrosomal microtubules. The function of the CAMSAP proteins upon spindle assembly remains unknown, as these do not exhibit evident localization to spindle microtubules. Here, we demonstrate that CAMSAP2, but not CAMSAP3, is required for spindle assembly upon mitotic entry. CAMSAP2 knockout (KO) Caco-2 cells showed a delay in mitotic progression, whereas CAMSAP3 KO cells did not. The spindle in CAMSAP2 KO cells was short and displayed a reduced microtubule density, particularly around chromosomes. This indicated a loss of bridging fibers, which are known to assist alignment of sister kinetochores through interaction with kinetochore fibers. Consistent with this, live-cell imaging of CAMSAP2 KO cells captured slow elongation of the anaphase spindle and errors in chromosome segregation. Therefore, we propose that CAMSAP2 ensures efficient reorganization of cytoplasmic microtubules into the mitotic spindle through constructing bridging fibers that assist faithful segregation of sister chromatids.